2016
DOI: 10.1245/s10434-016-5635-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of FLAIR Volume Changes in Glioblastoma and Prediction of Survival

Abstract: OS correlated with the immediate postoperative T1Gd-EOTR measured by enhanced T1 MRI, but not by FLAIR volume. Diminished abnormal FLAIR volume at 3 months post-surgery was associated with OS benefit when FLAIR-RTV was <19.3 cm or <46 % of baseline. These threshold values provide a new radiological variable that can be used for prediction of OS in patients with glioblastoma immediately after completion of standard chemoradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…41 These issues led to the development of the hyperintensity on post-treatment FLAIR imaging, relative to baseline, are correlated with improved survival. 35 Furthermore, some glioblastomas demonstrate imaging changes consistent with progression under the Macdonald criteria, but upon repeat surgical intervention, viable tumor cannot be identified in the resection specimen, suggesting that the adjuvant treatment may actually be having a positive effect that eludes detection on conventional imaging. This finding, termed "pseudoprogression," Axial post-contrast T1 (T1CE) images at 8 months.…”
Section: Discussionmentioning
confidence: 99%
“…41 These issues led to the development of the hyperintensity on post-treatment FLAIR imaging, relative to baseline, are correlated with improved survival. 35 Furthermore, some glioblastomas demonstrate imaging changes consistent with progression under the Macdonald criteria, but upon repeat surgical intervention, viable tumor cannot be identified in the resection specimen, suggesting that the adjuvant treatment may actually be having a positive effect that eludes detection on conventional imaging. This finding, termed "pseudoprogression," Axial post-contrast T1 (T1CE) images at 8 months.…”
Section: Discussionmentioning
confidence: 99%
“…Aerts et al found significant prognostic value of a radiomic CT signature developed for overall survival that validated across multiple independent cohorts of patients with lung and head & neck cancer [49]. Prognostic value across several cancer types has been also observed in a radiomic PET signature [58,59], In colorectal cancer, a seminar study by Huang et al described a radiomics nomogram to predict lymph node metastases [60].…”
Section: Radiomics For Predictive Disease Modelingmentioning
confidence: 99%
“…Hereby, the goal is to quantify the imaging phenotype of a tumor to inform treatment decisions [49]. As genomics refers to the collectivity of all genes within a cell, radiomics refers to the collectivity of all quantitative radiographic features of a subject of interest.…”
Section: Radiomicsmentioning
confidence: 99%
See 2 more Smart Citations